The vision of the managers of enterprises of lodging certificates in sustainability by NBR 15401:2006 - Oliveira, Murilo de Alencar Souza; Rossetto, Adriana Marques (Revista de Administração da UFSM, 2014)
This article aimed to understand the influence of social and environmental practices (sustainable) in strategic decision-making of national accommodation establishments (AE), upon perceptions of their managers. The study was conducted with a qualitative approach using field surveys and exploratory research. The sample was compound by every AE certified by the Brazilian Standard Recorded (NBR) 15401:2006 (Lodging - System of Sustainability Management) until august/2012. The 6 AE identified are located only in three tourist destinations (Armação dos Búzios/RJ, Lençóis /BA and Canela /RS) and they were visited for observation of the practices adopted and interviews with their managers. The results appoint that the sustainable decision stemmed from awareness of managers, of influence of government programs and of marketing (competitive differential), of sustainability (reconcile practices with the standard) and managerial (professionalism) goals. The strategic decision on organizational performance generated positive impacts on the image and in the cost reduction. The main facilitators identified were the subsidies and the support of the consultants, and the complicating factors were the discontinuity of government programs, the level of requirements of the standard and the absence of references to sustainability and professional qualify in the segment of lodging.